Strategi Pengembangan Usaha Pada UMKM Rumah Tenun Nggaliwara Melalui Pelatihan Digital Marketing dan Pembukuan Keuangan Berbasis Digital - Ita Purnama; Tri Wahyuni Alifah; Salimatul Uyun (Indo Publishing, 2026)
Rumah Tenun Nggaliwara is a Micro, Small, and Medium Enterprise (MSME) engaged in the provision and marketing of traditional Bima weaving products. In developing its business, the partner faced challenges related to suboptimal digital marketing and manual financial record-keeping practices. This Community Service Program aimed to improve the partner’s ability to utilize digital technology for marketing and financial management.The methods employed consisted of planning, implementation and evaluation stages through observation, training, and mentoring activities. Digital marketing training was conducted using the Store.link website, which integrates product catalogs and business social media accounts, while digital bookkeeping training was carried out using Google Spreadsheet to record income, expenses, and business profits. The results showed that the partner successfully created and managed a Store.link account connected to business social media platforms and product catalogs. In addition, the partner was able to develop a digital bookkeeping system using Google Spreadsheet to record financial transactions in a more structured and systematic manner. This program successfully enhanced the partner’s capability in utilizing digital technology for marketing and financial management, thereby supporting more effective and sustainable business development.